A novel specific duplex real-time RT-PCR method for absolute quantitation of Grapevine Pinot gris virus in plant material and single mites - Morán, Félix; Olmos, Antonio; Lotos, Leonidas; Katis, Nikolaos; Glasa, Miroslav; Predajna, Lukas; Ruiz-García, Ana B. (PLOS ONE, 2018)
Grapevine Pinot gris virus (GPGV) is a widely distributed grapevine pathogen that has been associated to the grapevine leaf mottling and deformation disease. With the aim of better understanding the disease epidemiology and providing efficient control strategies a specific and quantitative duplex TaqMan real-time RT-PCR assay has been developed. This method has allowed reliable quantitation of the GPGV titer ranging from 30 up to 3 x 108 transcript copies, with a detection limit of 70 viral copies in plant material. The assay targets a grapevine internal control that reduces the occurrence of false negative results, thus increasing the diagnostic sensitivity of the technique. Viral isolates both associated and non-associated to symptoms from Greece, Slovakia and Spain have been successfully detected. The method has also been applied to the absolute quantitation of GPGV in its putative transmission vector Colomerus vitis. Moreover, the viral titer present in single mites has been determined. In addition, in the current study a new polymorphism in the GPGV genome responsible for a shorter movement protein has been found. A phylogenetic study based on this genomic region has shown a high variability among Spanish isolates and points to a different evolutionary origin of this new polymorphism. The methodology here developed opens new possibilities for basic and epidemiological studies as well as for the establishment of efficient control strategies.